The Anation Kinetics of cis[Co(en)2(H2O)2](NO3)3 by Anthranilic Acid in Aqueous Medium - SRINIVAS, B.; RADHAKRISHNA REDDY, M.; CHANDRA PAL, A.V. (Asian Journal of Chemistry, 2010)
The detailed anation kinetics of cis[Co(en)2(H2O)2] (NO3)3 by anthranilic acid has been studied as a function of substrate complex concentration, temperature, ionic strength, pH and medium dielectric constant. It is observed that increasing ionic strength does not have any effect on the rate constant and the anation rate decreases with the increase of pH. Plots of 1/Kobs vs. 1/[Anth]- was linear with positive intercept at different temperatures indicating [Co(en)2(Anth)]2+ formation. Activation parameters have been evaluated from Eyring plot and a dissociative interchanging mechanism has been suggested, which is supported by the decrease of reaction rate with increase in dielectric constant. The Kobs values of [Co(en)2Anth]2+ are in good agreement with the first order rate law with respect to cis[Co(en)2(H2O)2](NO3)3.